(untitled) (Window of Public Health Journal, 2025)
Musculoskeletal Disorders (MSDs) encompass a range of symptoms or disorders affecting the muscles, tendons, ligaments, cartilage, nervous system, bone structure, and blood vessels. This study aims to determine the factors associated with complaints of Musculoskeletal Disorders (MSDs) in port workers at the Bulog Warehouse in Makassar City. The practical implications of this study’s findings can have a significant impact on occupational safety measures. This study employs a quantitative approach and utilizes a cross-sectional method. The sampling technique employed in this study was total sampling, with a sample size of 52. The results showed a relationship between age and complaints of Musculoskeletal Disorders, with a value (p = 0.003), length of service (p = 0.004), work posture (p = 0.003), and smoking habits (p = 0.041). This study concludes that there is a relationship between age, length of service, work posture, and smoking habits with complaints of Musculoskeletal Disorders in port workers. Meanwhile, no relationship was found between the load weight variable and musculoskeletal disorders in port workers.